Molecular cloning and expression analysis of CONSTANS-LIKE 2 in Mucuna bracteate DC. in different tissue and at low temperature - Sharif, Misfahulhairah (2021)
The flowering signals were perceived by angiosperms for the transition from vegetative to reproductive state at their apical tissue. The transition was triggered by environmental conditions and the internal regulation of various genes. Plants are capable of integrating environmental changes such as photoperiod and temperature into their developmental program. Mucuna bracteata is a legume originated from North India and is planted as a cover crop in the oil palm and rubber plantations in Malaysia. This legume is able to grow well locally but unable to produce flowers. Non-flowering M. bracteata plants may not perceive the flowering signals to initiate the reproductive phase due to environmental differences. This study is the first report on the cloning of a putative flowering gene, CONSTANS-LIKE 2 (COL2) from the leaves of M. bracteata. In this study, the MbCOL2 sequence with the length of 1335bp was successfully identified and cloned. MbCOL2 protein (335 amino acid residues) consisted of two BBOX domains, a CCT domain and a VP motif. The bioinformatic analysis on the unpublished transcriptome data showed that 13 COL protein members were present in the M. bracteata genome which had been classified into Groups 1, 2 and 3. To understand the molecular regulation of this gene in locally grown M. bracteata, the expression analysis of MbCOL2 in different tissues of M. bracteata seedlings and in response to low temperature was carried out using real time PCR. MbCOL2 expression in all selected tissues; leaf, shoot apical meristem and stem of 2-month, 6-month and 12-month old seedlings showed that MbCOL2 was expressed at the early stage of the plant growth. However, a higher abundance of MbCOL2 expression was detected in the leaf tissues as reported previously in other reference species. Meanwhile, the expression of MbCOL2 was increased by low temperature. However, the actual molecular mechanism of the flowering initiation of locally grown M. bracteata is still unknown. In the future, identification and expression profiling of various flowering genes can be performed to further understand the flowering induction in M. bracteata.